Use of glucose biosensors to measure extracellular glucose exudation by intertidal microphytobenthos in southern Tasmania. Issue 3 (19th April 2018) - McMinn, Andrew; Lee, Shihong
Abstract : Micro glucose biosensors were used to measure net extracellular glucose produced by natural microphytobenthos and three diatom cultures ( Amphora coffeaeformis, Navicula menisculus, Nitzschia longissima ) from southern Tasmania, Australia. They were exposed to a light gradient in either nutrient‐replete or nutrient‐limiting conditions. Glucose exudation in the natural communities increased with increased light but the response in the cultures was variable. Similarly, nutrient‐replete conditions elicited lower rates of glucose exudation in the natural communities but produced variable species‐specific responses in the cultures. Increased glucose exudation mostly correlated with a reduction in maximum quantum yield (Fv /Fm ). The same trend was observed in the natural communities for relative maximum electron transfer rates (rETRmax ) but responses in the cultures were again variable and species‐specific. Responses of the three species to increased light and nutrient deficiency were variable, although glucose exudation, Fv /Fm and rETRmax was mostly lower in the nutrient‐limited media. In a second set of experiments species/communities were treated with/without antibiotics. In the dark, glucose concentrations in treatments with antibiotics remained unchanged, while in those with bacteria, it fell rapidly. In the sediment communities, glucose consumption in the dark was ~25% the rate of exudation at the highest light level. In culture, exudation rates were up to 100% greater than those with active bacteria. Rates of glucose consumption in the dark in the antibiotic–treated samples were negligible and up to 10 4 times lower than those with active bacteria. These results demonstrate the important role extracellular glucose exudation has on maintaining an active microbial loop.